The first complete mitochondrial genome of Loimia arborea (Polychaeta: Terebellidae) and phylogenetic analysis - Xiong-hui Xu; Chao-yang Luo; Yuan Mu (Mitochondrial DNA. Part B. Resources)
In order to understand the molecular insights within the Terebellida, the complete mitochondrial genome of Loimia arborea was sequenced. The mitochondrial genome is 16,023 bp, with 13 protein-coding genes (PCGs), 23 transfer RNA (tRNA) genes, two ribosomal RNA (rRNA) genes, and a non-coding region (D-loop). Notably, two adjacent copies of methionine tRNA genes (trnMs) were detected. The phylogeny of Terebellida was constructed based on 13 PCGs from 13 species, two main clades were strongly supported, i.e., Cirratuliformia (clade A) and Terebelliformia (clade B). And the monophyly of the Terebellidae was restored.